Socio-Cultural Meanings of Special Children Names in The Luba Culture of Kasaï - Betu, Donat Nkuna; Benjamin Kalonga Kanumbedia (JOURNAL OF DIGITAL LEARNING AND DISTANCE EDUCATION, 2023)
This article approaches the correlations between the names of special children and their birth circumstances. We have used the lexical-pragmatic theory to show how context and circumstance of births contribute to the names ’meanings. This chapter considers recent work on lexical meaning developed within relevance theory which has been described using the term lexical pragmatics. This work focuses on how words are understood in context. It examines the socio-cultural significances of special children names in Tshiluba of Kasaï (L31), the cultural language of Luba people of Kasaï and one of the four national languages in Democratic Republic of Congo. Traditionally in the Luba culture of Kasaï, the naming custom of special children depends on the contexts and circumstances surrounding their births.